Impact of Prior Brain Injury on Concussion Recovery in Military Personnel: Evaluation of Timing Between Concussions. Issue 6 (15th November 2021) - Remigio-Baker, Rosemay A.; Babakhanyan, Ida; Gregory, Emma; Cole, Wesley R.; Ettenhofer, Mark L.; West, Therese; Qashu, Felicia; Mullins, Lynita; Bailie, Jason M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To evaluate the potential impact of timing between the current and the most recent previous concussions on symptom severity among acutely concussed active duty military Service members (SMs). Setting: Three military installations. Participants: Eighty-four SMs aged 18 to 44 years who sustained a concussion within 72 hours of enrollment. No previous concussion within 1 year preenrollment. Design: Longitudinal study with enrollment within 72 hours of injury, and follow-up at 1 week and 1 month postinjury. Main Measures: Lifetime concussion history (yes/no) and recency of the latest concussion (no history, relatively more recent [1 to <6 years ago], and more remote [6+ years ago]) from the current concussion using the Ohio State University Traumatic Brain Injury Identification Method–Interview Form. Symptom severity (total and by categories: cognitive, affective, somatosensory, vestibular) at all time points using the Neurobehavioral Symptoms Inventory. Results: Concussion history assessed as having any previous concussion was not found significantly related to symptom severity (total or by categories) following a current concussion. However, when timing between concussion was taken into account, time since previous concussion was significantly related to symptomatology, whereby those with relatively more recent previous concussion had greater total symptoms within 72 hours of injury and at 1 week postinjury (though not at 1 month) than those with more remote previous concussion (≤72 hours: difference = 15.4, 95% CI = 1.8 to 29.1; 1 week: difference = 15.2, 95% CI = 1.2 to 29.2) or no history (≤72 hours: difference = 11.6, 95% CI = 0.4 to 22.8; 1 week: difference = 13.9, 95% CI = 2.4 to 25.4). When evaluated by symptom category, this relationship was particularly important on affective and somatosensory symptoms. Conclusion: In recently concussed active duty SMs, the timing between the current and previous concussions may be an important factor in determining prognosis. Clinical assessment of concussion history that accounts for the timing of the most recent event may be necessary to identify patients who may require a more conservative plan of care and more gradual return to activity in the acute recovery stage.